2020
DOI: 10.1080/03057070.2020.1773721
|View full text |Cite
|
Sign up to set email alerts
|

Changing Livelihoods in Rural Eastern Cape, South Africa (2002–2016): Diminishing Employment and Expanding Social Protection

Abstract: Despite long-standing patterns of agrarian change in South and Southern Africa, rural locales remain home to millions of people, characterised by widespread poverty and vulnerability. This is evident in South Africa's former 'homelands', the site where this study examined changes in rural livelihoods over a 14-year period. Detailed survey data (collected in 2002 and 2016) from two villages in the Pondoland region of Eastern Cape province, and augmented by in-depth fieldwork, are analysed to explore the drivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
4
10
0
Order By: Relevance
“…The Eastern Cape was selected for this study because it has a large smallholder farming sector operating on communal lands and because deagrarianisation processes are well advanced [6,23,24]. Spanning 169,580 km 2 , the Eastern Cape is the second-largest province in South Africa, which underpins its biophysical heterogeneity.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…The Eastern Cape was selected for this study because it has a large smallholder farming sector operating on communal lands and because deagrarianisation processes are well advanced [6,23,24]. Spanning 169,580 km 2 , the Eastern Cape is the second-largest province in South Africa, which underpins its biophysical heterogeneity.…”
Section: Study Areamentioning
confidence: 99%
“…Despite these concerns about food security, deagrarianisation processes are well advanced in the communal land areas of South Africa [6,7,22], particularly in the Eastern Cape [6,23,24], which is the poorest province in South Africa. Of the 17 empirical studies summarised by Shackleton et al [6], 15 showed a net decline in the area of fields cultivated over the study period.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with better access to market, farmers might also opt for diversified household strategies to compensate the risk of low agricultural productivity with off-farm income (Ellis 1998, Ellis andFreeman 2004). These dynamics, here captured by the "risk aversion" cognitive archetype, represent an underlying factor across all spatial archetypes in Uganda, and also found in other African contexts (Hajdu et al 2020). This type of farmer's choice might also prove a resilient strategy for local communities (Ellis 1998), although reduced investment in agriculture might lead to land abandonment and further land degradation.…”
Section: Regional Barriers and Implications For Policiesmentioning
confidence: 99%